1974
DOI: 10.1071/ch9740241
|View full text |Cite
|
Sign up to set email alerts
|

Non-additivity of intermolecular forces: effects on the fourth virial coefficient

Abstract: In this paper we give the results of computing the effect of non-additivity of long range forces on the fourth virial coefficient of a Lennard-Jones 12-6 gas. We have considered only dipolar effects but have included all terms up to the fourth order of perturbation theory. We have also calculated the effect of the fourth-order triple-dipole term on the third virial coefficient. For the fourth virial coefficient we find that the dispersion non-additivity, while being positive at low reduced temperatures, goes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 0 publications
0
29
0
1
Order By: Relevance
“…[34] Forn eon it was shown that already the classical triple-dipole (Axilrod-Teller) term is agood approximation in the long range.H ence we chose the four-body contribution derived from the classical Drude model [35,36,51,52] whereũ ij is the unit vector in direction from atom i to atom j.T he prefactor w was chosen according to Johnsson and Spurling (corrected for am issing factor of 8), [51] that is, w = À(45/32)ca 4 with as caling factor [53] c = 0.6963 and the dipole polarizability a = 11.07 a.u. and R ij being the internuclear distance of the dimer with atoms i, j.F or the three-body potential we took the potential of Cencek et al evaluated at the CCSDT(Q) level of theory including scalar relativistic effects.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…[34] Forn eon it was shown that already the classical triple-dipole (Axilrod-Teller) term is agood approximation in the long range.H ence we chose the four-body contribution derived from the classical Drude model [35,36,51,52] whereũ ij is the unit vector in direction from atom i to atom j.T he prefactor w was chosen according to Johnsson and Spurling (corrected for am issing factor of 8), [51] that is, w = À(45/32)ca 4 with as caling factor [53] c = 0.6963 and the dipole polarizability a = 11.07 a.u. and R ij being the internuclear distance of the dimer with atoms i, j.F or the three-body potential we took the potential of Cencek et al evaluated at the CCSDT(Q) level of theory including scalar relativistic effects.…”
Section: Computational Detailsmentioning
confidence: 99%
“…and R ij being the internuclear distance of the dimer with atoms i, j.F or the three-body potential we took the potential of Cencek et al evaluated at the CCSDT(Q) level of theory including scalar relativistic effects. [34] Forn eon it was shown that already the classical triple-dipole (Axilrod-Teller) term is agood approximation in the long range.H ence we chose the four-body contribution derived from the classical Drude model [35,36,51,52] whereũ ij is the unit vector in direction from atom i to atom j.T he prefactor w was chosen according to Johnsson and Spurling (corrected for am issing factor of 8), [51] that is, w = À(45/32)ca 4 with as caling factor [53] c = 0.6963 and the dipole polarizability a = 11.07 a.u. taken from experimental measurements.…”
Section: Computational Detailsmentioning
confidence: 99%
“…32 However, expressions for nonadditive corrections have been reported only for the third through fifth virial coefficients. 33,34 Recently, Hellmann and Bich 35 presented a new derivation of the virial expansion, which is not restricted to pairwise-additive potentials. Furthermore, they provided explicit formulae for the numerical evaluation of the virial coefficients up to B 8 in terms of sums of newly defined cluster diagrams.…”
Section: Introductionmentioning
confidence: 99%
“…8 The third virial coefficient, B 3 , is represented as the sum of additive and nonadditive parts, as in…”
Section: Formulas and Methodsmentioning
confidence: 99%